Capital Structure and Asset Structure Decisions: Strategies for Improving Company Performance for Sustainable Business - Meliza , Juli; Mulyani, Mulyani; Fathimah, Vidya; Devi, Syahrani; Khairani, Syahrida (Adpebi Science Series, 2024)
This study aims to evaluate the impact of capital structure and asset structure decisions on the performance of PT. Summarecon Agung Tbk and PT. Agung Semesta Sejahtera Tbk. This research is descriptive quantitative and uses secondary data from the companies' websites, from 2019 to 2023. A panel least square approach is used to estimate the effect of capital structure and asset structure decisions on company performance. The results show that capital structure and asset structure decisions significantly influence company performance (ROA). The relationship between asset structure and equity return can vary depending on different contexts and industries, and the findings indicate that asset structure does not affect ROE. This supports the idea that while asset structure may impact return on assets, its effect on return on equity may be minimal. The results obtained will assist investors and potential investors in making financing policies that maximize performance. Similarly, the government and other policymakers review capital market performance. Companies that can effectively manage their capital and assets can not only enhance their financial and operational performance but also ensure long-term sustainability and competitiveness in an increasingly competitive market. This study contributes to the formulation of corporate financing policies and corporate finance literature, particularly in the property sector.